Pan Made Me a Hooligan - Johnson, Kim (Trinidad Express)
Steelband was created and developed through the love of countless young men who nurtured and protected it in its infancy. "I did never like steelband, it was a hooligan thing and I was not one," recalls Victor "Sufferer" Hercules, one of the stalwarts of Crossfire steelband in St James.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago